2015
DOI: 10.1007/s10529-015-1903-4
|View full text |Cite
|
Sign up to set email alerts
|

Purification and functional characterization of thermostable 5-aminolevulinic acid synthases

Abstract: Thermostable ALASs were found in thermophilic organisms and this paves the way for developing cell free processes for enzymatic production of ALA from bulk chemicals succinate and glycine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…The protocol for enzyme production was identical to the one described by Meng et al To produce the enzymes, the recombinant cells were cultured in 4 mL LB medium with 50 µg mL –1 kanamycin medium at 37°C and 220 rpm for 12 h. The resulting seed culture was transformed into 200 mL of freshly prepared LB medium with 1% inoculum in 1 L flasks. When the culture OD 600 reached 0.6–0.8, 0.5 mmol L –1 isopropyl β‐D‐1‐thiogalactopyranoside (IPTG; Sangon biotech, Shanghai, China) was added for induction, and protein expression was conducted at 16°C, 220 rpm for 16–18 h. The protein‐expressing cells were harvested and washed with binding buffer A (Tris‐HCl 50 mmol L –1 , NaCl 150 mmol L –1 and imidazole 20 mmol L –1 , pH 7.5) by centrifugation at 5000× g for 20 min at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…The protocol for enzyme production was identical to the one described by Meng et al To produce the enzymes, the recombinant cells were cultured in 4 mL LB medium with 50 µg mL –1 kanamycin medium at 37°C and 220 rpm for 12 h. The resulting seed culture was transformed into 200 mL of freshly prepared LB medium with 1% inoculum in 1 L flasks. When the culture OD 600 reached 0.6–0.8, 0.5 mmol L –1 isopropyl β‐D‐1‐thiogalactopyranoside (IPTG; Sangon biotech, Shanghai, China) was added for induction, and protein expression was conducted at 16°C, 220 rpm for 16–18 h. The protein‐expressing cells were harvested and washed with binding buffer A (Tris‐HCl 50 mmol L –1 , NaCl 150 mmol L –1 and imidazole 20 mmol L –1 , pH 7.5) by centrifugation at 5000× g for 20 min at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have cloned and identified ALASs from a variety of species and used them for the construction of 5-ALA producing strains. However, most of the natural ALAS suffers from low catalytic efficiency and/or serious feedback inhibition by heme [15,[57][58][59], which would limit their practical application in bioproduction of 5-ALA (Zhang et al [15]). Tan et al obtained two R. palustris ALAS variants (H29R and H15K) with moderately enhanced thermostability and released feedback inhibition via computer-aided rational enzyme engineering.…”
Section: Engineering Of Alas For Releasing Heme Feedback Inhibition A...mentioning
confidence: 99%
“…palustris, R. sphaeroides, Rhodoblastus acidophilus, Laceyella sacchari, and Caulobacter crescentus, has been characterized. To broaden the spectrum of available ALASs and identify more efficient ALASs, we performed a brief phylogenetic analysis on a pool of 2440 bacteria ALASs candidates, categorizing them into three phylogenetic groups after multiple sequence alignments (Figure S1). We subsequently selected 16 ALASs candidates (including the previously characterized ALASs) randomly from the three groups, realigned the sequences, and constructed a maximum likelihood tree (Figure A).…”
Section: Resultsmentioning
confidence: 99%